Legal Views on Menstrual Delays in Ramadhan - Mukhtar, Rasya; Ning, Syarifah; Hasanah, Cut (PT. Riset Press International, 2023)
Fasting during Ramadan is obligatory for every Muslim/Muslimah who is mature, intelligent, clean from menstruation and childbirth for women, and who does not have a valid reason, such as travelers and sick. Meanwhile, menstruation is a natural process that occurs in every woman. With the current breakthroughs in medical science, drugs have emerged that can delay menstruation experienced by women, making it possible to carry out Ramadan fasting without obstacles. This type of research is library research (library research). With a historical approach. The data collection method is using a literature study, in which in this section the author will collect MUI fatwas and fiqh books on the topic being researched. Then read and trace the legal istinbath method. The results of the study show that the negative impact of this drug affects the body's work system, so its use in an inappropriate place is not recommended. While the positive impact on health, the authors assume there is no. Because this drug aims to block the natural cycle that occurs in women. Then the use of drugs that are not on target or used in the long term or made from inappropriate ingredients, will certainly have implications for the body. Meanwhile, Nash has not yet regulated the legal status of delaying menstruation. So ijtihad is needed in this case by looking at the benefits. If you delay your menstrual period using drugs, you will examine the side effects. If it causes harm to the body, it is better to avoid it. However, if it does not cause harm then it is permissible. As stated in the MUI fatwa No. 2 of 1979.